ADMINISTRATION OF ADVANCED TRAINING FOR AVIATION EXECUTIVES - Bezzubov, Dmytro; Dobkina, Kateryna; Huseynova, Fatima (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The article is aimed the formation of modern approaches and administration principles regarding advanced training of aviation enterprise managers, the outline of pedagogical models and qualitative content of advanced training programs, the development of a single administrative mechanism to ensure the effectiveness of such pedagogical activities. Methods of research: the main scientific methods of formal logic, system analysis and the classification method were used during the work. The method of system analysis is applied accordingly to determine special and general mechanisms for ensuring the process of administration related to upgrading the qualifications of managers of aviation enterprises. The method of formal logic allows us to determine scientific views on the categories of pedagogical methods, legal support and possible results of training of managers of aviation enterprises. The method of classifications has enabled determining the ways of further improvement regarding the institutional foundations of the administration of advanced training of managers of aviation enterprises. Results: the study of the issue of the legal foundations of the administration of advanced training for the managers of aviation enterprises is part of the study of the problems related to legal pedagogy, economic and aviation law. The results presented in this scientific article allow us to determine further steps for solving the organizational and legal problems of organizing the training of managers of aviation enterprises. Discussion: the problems of advanced training of managers of aviation enterprises are applied from the standpoint of the development of legal pedagogy, economic and aviation law.